Increasing Local Biomass Waste for Independent Fish Feed Production - Hamka, Muhammad Subhan; Triayu Rahmadiah; Ikromatun Nafsiyah; Harry Prayoga Setyawan; Arif Rahman Azis; Asih Sriyanti; Novendra Andika Pratama; Lestari, Siti (Universitas Islam Lamongan, 2026)
Bengkulu Province has extensive potential in the fisheries, agriculture, and forestry sectors. However, the fisheries sector currently faces a dependency on commercial feed. The use of waste materials is expected to reduce dependence on commercial feed. The research method used was a Completely Randomized Design with several research treatments. In this study, the best treatment was the use of Fermented Vegetable Waste + 15% Fermented Coffee Husk (B2), which showed quite efficient FCR, SGR, and PER results.